Severe Inhibition of Long-Chain Acyl-CoA Enoylhydratase (EC 4.2.1.74) in a Newborn Foal Suffering From Atypical Myopathy - Sander, Johannes; Terhardt, Michael; Janzen, Nils (Frontiers in Veterinary Science, 2021)
In horses, congenital defects of energy production from long-chain fatty acids have not been described so far. In contrast, inhibition of fatty acid degradation caused by the toxins hypoglycin A and metylenecyclopropylglycine from various maple species are observed frequently. These non-proteinogenic aminoacids are passed on placentally to foetuses or with collostrum or milk to newborn foals. Nevertheless, newborn foals become very rarely symptomatic. Vertical transmission apparently is not sufficient to induce clinical disease without a particular genetic constellation being present. One of these rare cases was investigated here using samples from a mare and her foal. Intoxication by hypoglycin A and metylenecyclopropylglycine is also of interest to human pathology, because these toxins have caused fatal poisonings after consumption of certain fruits many times, especially in children. Maple toxins, their metabolites and some short-chain acyl compounds were quantified by ultrahigh-pressure liquid chromatography/tandem mass spectrometry. An comprehensive spectrum of long-chain acylcarnitines was prepared using electrospray ionization tandem mass spectrometry. Organic acids and acylglycins were determined by gas chromatography mass spectrometry. For evaluation, results of other horses poisoned by maple material as well as unaffected control animals were used. In the serum of the foal, hypoglycin A was detected at low concentration only. Toxin metabolites reached less than 3.5% of the mean of a comparison group of horses suffering from atypical myopathy. The spectrum of acylcarnitines indicated enzyme inhibition in short-chain and medium-chain regions typical of acer poisoning , but the measured concentrations did not exceed those previously found in clinically healthy animals after maple consumption. The values were not sufficient to explain the clinical symptoms. In contrast, a remarkably strong enrichment of tetradecenoylcarnitine and hexadecenoylcarnitine was observed. This proves a blockade of the long-chain enoyl-CoA hydratase (EC 4.2.1.74). Vertical transfer of maple toxins to a newborn foal is sufficient for induction of clinical disease only if there is an additional specific reactivity to the active toxins. This was found here in an inhibition of long-chain enoyl-CoA hydratase. Isolated dysfunction of this enzyme has not yet been reported in any species. Further studies are necessary to prove a specific genetic defect.